Didactics in Virtual Learning Environments: towards the digital transformation of teacher training - Coreas Bonilla, Carlos Vinicio (Revista Saberes Educativos, 2024)
This article presents a systematization of the experience of Didactic training in Virtual Learning Environments (DEVA) carried out by the National Institute for Teacher Training (INFOD) and the National Directorate for Teacher Training (DNFD) of the Ministry of Education, Science and Technology (MINEDUCYT) of El Salvador, during the year 2021, within the framework of the Covid-19 pandemic. Technical personnel closely linked to the training process by INFOD and DNDF were interviewed and institutional archival and online documents were reviewed. A brief conceptual framework was incorporated to support the analysis.